2021
DOI: 10.3389/fendo.2021.609240
|View full text |Cite
|
Sign up to set email alerts
|

A Focused Review of the Metabolic Side-Effects of Clozapine

Abstract: The second generation antipsychotic drug clozapine represents the most effective pharmacotherapy for treatment-resistant psychosis. It is also associated with low rates of extrapyramidal symptoms and hyperprolactinemia compared to other antipsychotic drugs. However, clozapine tends to be underutilized in clinical practice due to a number of disabling and serious side-effects. These are characterized by a constellation of metabolic side-effects which include dysregulation of glucose, insulin, plasma lipids and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 181 publications
(166 reference statements)
0
25
0
1
Order By: Relevance
“…Many of the side effects encountered with clozapine are dose-dependent including sedation, tachycardia, hypersalivation, enuresis, constipation, delirium, obsessive-compulsive symptoms, seizures, and orthostatic hypotension[ 81 , 120 , 138 ] Among all antipsychotics, the prevalence of metabolic dysfunction or metabolic syndrome is the highest for clozapine and olanzapine[ 81 , 126 , 127 , 132 , 139 ]. Whether metabolic side effects are also dose-dependent is not clear[ 81 , 138 ].…”
Section: Preventing Resistance To Clozapine Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the side effects encountered with clozapine are dose-dependent including sedation, tachycardia, hypersalivation, enuresis, constipation, delirium, obsessive-compulsive symptoms, seizures, and orthostatic hypotension[ 81 , 120 , 138 ] Among all antipsychotics, the prevalence of metabolic dysfunction or metabolic syndrome is the highest for clozapine and olanzapine[ 81 , 126 , 127 , 132 , 139 ]. Whether metabolic side effects are also dose-dependent is not clear[ 81 , 138 ].…”
Section: Preventing Resistance To Clozapine Treatmentmentioning
confidence: 99%
“…However, systematic reviews and meta-analyses have indicated a dose-outcome association between clozapine and metabolic side effects, particularly with lipid levels and weight gain[ 140 , 141 ]. Risk factors for metabolic syndrome include higher baseline weight or body mass index, gender, non-White, possibly Asian ethnicity, and several genetic and peptide markers[ 126 , 127 , 136 , 139 , 142 ]. Somewhat paradoxically, metabolic disturbances are also associated with a reduction in symptoms[ 126 , 127 ].…”
Section: Preventing Resistance To Clozapine Treatmentmentioning
confidence: 99%
“…One study discovered a genetic overlap between the pathogenesis of schizophrenia and the mechanism of clozapine as an antipsychotic, indicating that if the mechanism of clozapine could be understood, valid therapeutic targets could be identified, and perhaps, schizophrenia's complex pathophysiology could be elucidated [3]. Researchers, however, reported associations between clozapine and adverse metabolic events-such as elevated cholesterol, blood glucose concentration, triglyceride levels, and body weight-and these events negatively influence medication compliance and health [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These findings therefore provide additional evidence that peripheral catecholamines may play a key role in the acute metabolic effects of antipsychotic drugs. The metabolic side-effects of antipsychotic drugs in clinical populations are now well established ( Allison et al, 1999 ; McEvoy et al, 2005 ; Newcomer, 2007 ; Kessing et al, 2010 ; Mitchell et al, 2013 ; Kim et al, 2017 ; Tumiel et al, 2019 ; Yuen et al, 2021a ), and animal studies have faithfully modelled these many of these effects, using comparable techniques that are commonly used in humans, including the GTT ( Monzillo and Hamdy, 2003 ). We and many other research groups ( Smith et al, 2008 ; Muller et al, 2010 ; Boyda et al, 2013a ; Boyda et al, 2014 ; Evers et al, 2017 ; Lord et al, 2017 ; Stefanidis et al, 2017 ; Oxenkrug and Summergrad, 2020 ; Sylvester et al, 2020 ; Shamshoum et al, 2021 ) routinely observe that antipsychotics generate acute glucose intolerance of an equivalent magnitude to that noted in human studies ( Albaugh et al, 2011 ) without a change in factors such as food intake or obesity, indicating a direct effect of the drugs on glucose dysregulation.…”
Section: Discussionmentioning
confidence: 99%